A Study of Using DTLS and CoAP protocols in the secure transfer of images in a cloud-based IoT system - دندة رضوان; احمد احمد; غدير رشا (Latakia University Journal -Engineering Sciences Series, 2021)
Nowadays, The Internet of Things (IoT) is considered to be a real revolution in the world of the Internet, especially with the appearance of cloud technology. Data transfer protocols are considered a key factor for communication between these things and the cloud, especially in real-time scenarios. Constrained Application Protocol (CoAP) is an important protocol used to transfer data between things and the cloud, but it suffers from not achieving any secure channel during the transmission process. Security is considered as one of the most important topics that must be taken into consideration, especially in some applications where the data sent from objects of different types are sensitive and need to be protected, as an example of those applications, those that deal with face recognition and tracking. This paper provides a proposal for securing CoAP protocol using the Datagram Transport Layer Security (DTLS) protocol in an IoT system designed to recognize faces based on the OpenCV library provided by the cloud. To achieve our goal, the proposed architecture was initially analyzed from the security point of view, after that we study the burden of using the DTLS protocol, as this was achieved by comparing the transmission of images with the presence and absence of protection, to show that the use of the DTLS protocol imposes a burden on things, as the power consumption increases by 12% and the processor usage time increases by almost twice.